Adaptation to acidic conditions that mimic the tumor microenvironment, downregulates miR-193b-3p, and induces EMT via TGFβ2 in A549 cells - Sadayuki Higashi; Munekazu Yamakuchi; Hirohito Hashinokuchi; Kazunori Takenouchi; Akito Tabaru; Yoko Oyama; Chieko Fujisaki; Kiyonori Tanoue; Teruto Hashiguchi (PLoS ONE, 2025)
The acidic tumor microenvironment plays a critical role in the malignant transformation of cancer cells. One mechanism underlying this transformation involves epithelial-mesenchymal transition (EMT). This is induced by prolonged exposure to acidic conditions. EMT is an essential process in cancer progression, with Transforming Growth Factor Beta (TGF-β) playing a central role in its induction. However, little was known about the factors regulating TGF-β under acidic conditions. This study aimed to elucidate the mechanism of EMT under acidic conditions and identify novel therapeutic targets to inhibit cancer cell migration and metastasis. Focusing on lung cancer, we explored microRNAs associated with EMT that were differentially expressed under acidic conditions in A549 cells and identified miR-193b-3p as a novel candidate. Under acidic conditions, miR-193b-3p expression decreased around days 3–14. Downregulation of miR-193b-3p promoted increased TGFβ2 expression, resulting in EMT changes in A549 cells. Our study suggests that the interaction between miR-193b-3p, TGFβ2, and the acidic tumor microenvironment promotes cancer EMT change. Understanding these interactions may not only enhance our biological comprehension of cancer, but also pave the way for the development of targeted therapies to inhibit cancer metastasis.